1993
DOI: 10.1111/j.1528-1157.1993.tb02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Toward Epilepsy Among Rural Tanzanian Residents

Abstract: Before a health education program can be established, one must first know what the target population believes and does with respect to the disease in question. Therefore, we performed a study among Tanzanian rural inhabitants to identify their knowledge, attitude, and practice (KAP) toward epilepsy: 3,256 heads of households (mean age 40.2 years, range 15-90 years; M/F ratio 1:1) were interviewed. Of the respondents, 32.9% said they had never seen a seizure; 67.7% said they did not know the cause of epilepsy; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 10 publications
6
69
3
2
Order By: Relevance
“…This finding similar to finding of study conducted in Tanzanian by (Rwiza et al 2007) who studied Knowledge, attitude and practice toward epilepsy among rural residents. They concluded that the low level of knowledge and misconceptions found among respondents, demonstrated the need for educational programs.…”
Section: Discussionsupporting
confidence: 80%
“…This finding similar to finding of study conducted in Tanzanian by (Rwiza et al 2007) who studied Knowledge, attitude and practice toward epilepsy among rural residents. They concluded that the low level of knowledge and misconceptions found among respondents, demonstrated the need for educational programs.…”
Section: Discussionsupporting
confidence: 80%
“…Questionnaires that evaluate the perception of epilepsy in many different social segments have been used by a great number of authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Although many limitations have been observed such as understanding the questions, diffi culty in achieving the right answer since there is a broad range of epilepsies, the tendency is to not expose negative positions on the subject and the non-validation of the instrument 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Negative public attitude toward epilepsy is a common phenomenon all over the world (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and is the major factor causing serious social discrimination against people with epilepsy. In general, those with epilepsy have considerable limitations in their interaction with and adaptation to their surroundings; some of them find social attitudes toward them more devastating than the disorder itself (11).…”
Section: Introductionmentioning
confidence: 99%